Combined Awake Craniotomy with Endoscopic Port Surgery for Resection of a Deep-Seated Temporal Lobe Glioma: A Case Report - Lance Bodily; Arlan H. Mintz; Johnathan Engh (Case Reports in Medicine)
The authors describe the combination of awake craniotomy and minimally invasive endoscopic port surgery to resect a high-grade glioma located near eloquent structures of the temporal lobe. Combined minimally invasive techniques such as these may facilitate deep tumor resection within eloquent regions of the brain, allowing minimum white matter dissection. Technical aspects of this procedure, a case outcome involving this technique, and the direction of further investigations for the utility of these techniques are discussed.